Phylogenetic analysis suggests that sociality is associated with reduced effectiveness of selection. Issue 2 (8th January 2016) - Settepani, Virginia; Bechsgaard, Jesper; Bilde, Trine
Abstract: The evolution of sociality in spiders is associated with female bias, reproductive skew and an inbreeding mating system, factors that cause a reduction in effective population size and increase effects of genetic drift. These factors act to decrease the effectiveness of selection, thereby increasing the fixation probability of deleterious mutations. Comparative studies of closely related species with contrasting social traits and mating systems provide the opportunity to test consequences of low effective population size on the effectiveness of selection empirically. We used phylogenetic analyses of three inbred social spider species and seven outcrossing subsocial species of the genus Stegodyphus, and compared dN/dS ratios and codon usage bias between social Inbreeding and subsocial outcrossing mating systems to assess the effectiveness of selection. The overall results do not differ significantly between the social inbreeding and outcrossing species, but suggest a tendency for lower codon usage bias and higher dN/dS ratios in the social inbreeding species compared with their outcrossing congeners. The differences in dN/dS ratio and codon usage bias between social and subsocial species are modest but consistent with theoretical expectations of reduced effectiveness of selection in species with relatively low effective population size. The modest differences are consistent with relatively recent evolution of social mating systems. Additionally, the short terminal branches and lack of speciation of the social lineages, together with low genetic diversity lend support for the transient state of permanent sociality in spiders. Abstract : Comparative studies of closely related species with contrasting social traits and mating systems provide the opportunity to test consequences of low effective population size on the effectiveness of selection empirically. We used phylogenetic analyses of inbred social spider species and outcrossing subsocial species of the genus Stegodyphus, and compared dN/dS ratios and codon usage bias between social inbred and subsocial outcrossing mating systems to assess the effectiveness of selection. The overall results suggest a tendency for lower codon usage bias and higher dN/dS ratios in the social inbreeding species compared with their outcrossing congeners consistent with theoretical expectations of reduced effectiveness of selection in species with relatively low effective population size.